2016
DOI: 10.18632/oncotarget.14182
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of expression of nuclear factor kappa-B/p65 in non-GCB DLBCL patients

Abstract: PurposeWe estimated the expression of nuclear factor kappa B/p65 in non-germinal center B-cell-like subtype diffuse large B-cell lymphoma, to investigate its relationship to clinicopathological features, and to further evaluate its prognostic value and clarify its impact on survival.ResultsAmong the 49 patients enrolled in this study, 14 (28.6%) had positive p65 expression. The negative p65 group had significantly better survival compared to the positive p65 group in terms of both the 3-year estimated OS (91.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…This is consistent with the findings of Kloo et al, Kasama et al 2014 [5], Foureau et al 2015 [21], Hallas et al 2019 [22], Odqavist et al [23], who have shown that constitutive activation of NF-κB is a common feature of ABC DLBCL cells [24]. The expression of nuclear factor kappa B/p65 in diffuse large B-cell lymphoma ABC subtype was significantly higher than the GCB in the current study [11]. This study clarified the role of NFκB [p65] in ABC DLBCL and so aids in determining the subgroup of non-GCB DLBCL for which this pathway will serve as a valuable therapeutic target.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with the findings of Kloo et al, Kasama et al 2014 [5], Foureau et al 2015 [21], Hallas et al 2019 [22], Odqavist et al [23], who have shown that constitutive activation of NF-κB is a common feature of ABC DLBCL cells [24]. The expression of nuclear factor kappa B/p65 in diffuse large B-cell lymphoma ABC subtype was significantly higher than the GCB in the current study [11]. This study clarified the role of NFκB [p65] in ABC DLBCL and so aids in determining the subgroup of non-GCB DLBCL for which this pathway will serve as a valuable therapeutic target.…”
Section: Discussionsupporting
confidence: 92%
“…Although patients who expressed NFκB [p65] in this study had higher incidence of extranodal involvement, presented more in later stages [III + IV], and had higher LDH levels and IPI score, yet most of the patients had low ECOG score between 0 to 1. They suggested that that NFκB [p65] is an independent predictor of survival in high risk non-GCB DLBCL [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GCB DLBCLs were found to express genes of germinal center B cells, such as CD10, LMO2, or BCL6, and frequently, they were associated with REL amplification, EZH2 mutation, or t (14;18) translocation [3,[7][8][9][10][11][12][13]. The pathogenesis of ABC DLBCLs was believed to be related to activation of the NF-κB signaling pathway via the B-cell receptor (BCR) pathway, but recent studies demonstrated that NF-κB may be expressed in both ABC and GCB DLBCL subgroups and is an adverse prognostic factor [7,[12][13][14][15][16][17][18][19][20]. TNFAIP3, CARD11, CD79B, CD79A, TRAF2, MYD88, and REL are the most commonly altered genes with an adverse impact in the ABC DLBCL subtype [7,12,13,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Under the stimulation of the above activators, IκBα is phosphorylated by the IκB kinase (IKK) and degraded via the ubiquitin-proteasome system. Then, the RelA/p50 dimers expose and translocate to the nucleus, leading to the transcription of target genes which may be involved in controlling cell cycle distribution and apoptosis occurrence 5,6 .…”
Section: Introductionmentioning
confidence: 99%